1997
DOI: 10.1002/(sici)1099-114x(199707)21:9<759::aid-er254>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the thermal response of latent heat storage systems

Abstract: SUMMARYLatent heat storage systems especially those employing organic materials have been reported to exhibit a rather slow thermal response. This is mainly due to the relatively low thermal conductivities of organic latent heat materials. This paper reports experiments carried out to investigate methods of enhancing the thermal response of paraffin wax heat storage tubes by incorporation of aluminium thermal conductivity promoters of various designs into the body of the wax. Heating and cooling runs were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 3 publications
(4 reference statements)
0
23
0
Order By: Relevance
“…Various techniques have been proposed to enhance the thermal conductivities of the PCMs, such as filling high-conductivity particles into PCMs [32], incorporating porous matrix materials into PCMs [33][34][35][36][37][38], inserting fibrous materials [39], as well as macro and micro encapsulating the PCMs [40,41] Bugaje [32] reported that the phase change time is one of the most important design parameters in latent heat storage systems and found adding aluminum additives into paraffin wax can significantly reduce the phase change time in heating and cooling processes. However, this method results in weight increasing and high cost of the system.…”
Section: Heat Transfer Enhancementmentioning
confidence: 99%
“…Various techniques have been proposed to enhance the thermal conductivities of the PCMs, such as filling high-conductivity particles into PCMs [32], incorporating porous matrix materials into PCMs [33][34][35][36][37][38], inserting fibrous materials [39], as well as macro and micro encapsulating the PCMs [40,41] Bugaje [32] reported that the phase change time is one of the most important design parameters in latent heat storage systems and found adding aluminum additives into paraffin wax can significantly reduce the phase change time in heating and cooling processes. However, this method results in weight increasing and high cost of the system.…”
Section: Heat Transfer Enhancementmentioning
confidence: 99%
“…In low-temperature latent heat storage systems, paraffin and hydrated salts are often used as heat storage media; most of these media suffer from the common problem of low thermal conductivity of approximately 0.2 and 0.5, respectively, which prolongs the charging and discharging period. Bugaje [2] reported that phase change time is the most important design parameter in latent heat storage systems. Suitable thermal conductivity parameters are used to provide a high thermal conductivity to the designed heat transfer rates.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable thermal conductivity parameters are used to provide a high thermal conductivity to the designed heat transfer rates. Bugaje [2] found that adding aluminum additives into paraffin wax can significantly reduce the phase change time in heating and cooling processes. Koh and Stevens [3] observed that the effectiveness of regenerative devices is increased by filling the flow passage with steel particles.…”
Section: Introductionmentioning
confidence: 99%
“…Air cooling is very demanding for the design of the air duct, and the temperature consistency of the cell monomer is not good because it is difficult to make the flow field consistent. Liquid cooling means that the heat transfer medium circulated in a battery group is 16 liquid. The liquid usually has a much larger heat transfer coefficient than air and a thinner liquid boundary layer which makes its effective thermal conductivity higher than air does.…”
Section: Overview Of Battery Thermal Management Systemmentioning
confidence: 99%
“…To overcome the shortcoming of low thermal conductivity and inflammable, many researcher improved the performance of the PCM by doping with other substances [16][17][18] . The research on the application of phase change materials used in the battery thermal management is late.…”
Section: Fig 17 Pcms Classification According To the Materials Propertymentioning
confidence: 99%